2018
DOI: 10.1002/cae.22042
|View full text |Cite
|
Sign up to set email alerts
|

Improving final grade prediction accuracy in blended learning environment using voting ensembles

Abstract: This paper deals with the comparative analysis of prediction classifiers in the blended learning environment. The model proposed in this paper predicts students’ final grades based on activities within different educational environments. A comparative study of classifier performance has been performed in order to determine the classifier most suitable for multiclass feature dataset. Important results for different classes have been obtained using different classifiers, and the majority vote scheme is subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The results revealed that reviewed articles made several contributions on predicting academic performance, identifying learning behaviours, and improving learning environments. With regards to predicting academic performance, machine learning-based predictive models was proven to be effective but with low portability across courses, whereas visualisation-based methods required teacher assistance [2,77]. Moreover, data variables effectiveness on performance prediction is based on course structure; however, social network metrics and variables related to LMS engagement, self-regulated learning, collaborative learning are found significantly correlated with academic performance [86,90,102].…”
Section: Rq1 and Rq2mentioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed that reviewed articles made several contributions on predicting academic performance, identifying learning behaviours, and improving learning environments. With regards to predicting academic performance, machine learning-based predictive models was proven to be effective but with low portability across courses, whereas visualisation-based methods required teacher assistance [2,77]. Moreover, data variables effectiveness on performance prediction is based on course structure; however, social network metrics and variables related to LMS engagement, self-regulated learning, collaborative learning are found significantly correlated with academic performance [86,90,102].…”
Section: Rq1 and Rq2mentioning
confidence: 99%
“…81. Understanding and predicting performance: To predict students' academic performance, random forest, linear and logistic regression, and ensemble modelling based predictive models provided satisfying results (over 70% accuracy)[2,51,77,80,81,102]. Similarly, a forecast learning outcome model (FLOM) was developed using interactive data to predict at-risk students…”
mentioning
confidence: 99%
“…that is widely used as it is simple and able to make fast predictions. It is suitable for small datasets that combine complexity with a flexible probabilistic model [24]. • Decision Tree (J48) a widely used in several multi-class classification that can handle missing values with high…”
Section: Performance Analysismentioning
confidence: 99%
“…Studies under EDM proposed several data mining approaches ( Chanlekha and Niramitranon 2018 ; Kaviyarasi and Balasubramanian 2018 ; Predić et al, 2018 ; Zaffar et al, 2018 ; Fernandes et al, 2019 ; Inyang et al, 2019 ; Li et al, 2019 ) to predict academic performance. In contrast to AIED, specific subject-related data were collected (e.g.…”
Section: Related Workmentioning
confidence: 99%
“…It has also been shown that effective feedback and action recommendations are essential for self-regulated learning (SRL) and are significantly correlated with students’ learning and performance ( Algayres and Triantafyllou 2020 ). Therefore, to address these challenges, a number of studies within the fields of learning analytics (LA), artificial intelligence in education (AIED) and educational data mining (EDM) have investigated how students’ self-regulation could be supported through, for instance, dashboards that provide predictive student performance ( Lakkaraju et al, 2015 ; Johnson et al, 2015 ; Kim et al, 2016 ; Marbouti et al, 2016 ; Akhtar et al, 2017 ; Chanlekha and Niramitranon 2018 ; Choi et al, 2018 ; Howard et al, 2018 ; Nguyen et al, 2018 ; Predić et al, 2018 ; Villamañe et al, 2018 ; Xie et al, 2018 ; Baneres et al, 2019 ; Bennion et al, 2019 ; Rosenthal et al, 2019 ; Nouri et al, 2019 ; D.). These studies employed various data mining, machine learning (ML), clustering and visualisation techniques on a diverse variety of learning management system (LMS) data sources to predict student success and failure in a course or in an entire academic year.…”
Section: Introductionmentioning
confidence: 99%